Effects of extraction methods of shiitake by-products on their antioxidant and antimicrobial activities in fermented sausages during storage. (September 2017) - Van Ba, Hoa; Seo, Hyun-Woo; Cho, Soo-Hyun; Kim, Yoon-Seok; Kim, Jin-Hyoung; Ham, Jun-Sang; Park, Beom-Young; Pil-Nam, Seong
Abstract: Two different solvents (water and ethanol/water at 50/50 ratio) were used for extraction of phenolic contents in shiitake by-products, and the antioxidant and antimicrobial efficacies of fermented sausages incorporated with these two extracts were investigated during storage. Also, shelf-life stability of fermented sausages fortified with these two extracts was compared with those fortified with BHT (0.02%) or nitrite (0.01%)/nitrate (0.005%). Significantly higher antioxidant activities (e.g., ferrous ion chelating and DPPH scavenging) and inhibitory capacity against lipid oxidation (e.g., TBARS reduction) were observed in the fermented sausages made with ethanolic extract (shiitake by-products extracted with ethanol/water) compared with those added with aqueous extract (extracted with water) or BHT, nitrite/nitrate and control throughout storage. The ethanolic extract treated-samples also showed a significantly slower increasing rate of total aerobic count (6.54–6.95 log10 cfu/g) than the ones treated with aqueous extract (6.74–7.16 log10 cfu/g) during storage. Otherwise, extract obtained from the ethanolic extract treated-samples had stronger antimicrobial activities against pathogens than the one obtained from aqueous extract treated-samples (e.g., minimum inhibitory concentrations, MIC = 2.05 & 3.64, 3.12 & 5.20 and 7.29 & 10.41 mg/mL for S. aureus, L. monocytogenes and E. coli O157, respectively). Especially, the antimicrobial activity against S. typhimurium (MIC = 37.50 mg/mL) was observed only in the extract of ethanolic extract treated-samples. Our study demonstrates that the extraction with ethanol/water solvent is a more effective method to obtain bioactive compounds enriched-extract which better improved the shelf-life stability of fermented sausages during storage without defects in quality in comparison to the extraction method with water. Highlights: The bioactivities of two shiitake stipes extracts in fermented sausages were compared. Extraction with ethanol/water resulted in higher phenols than extraction with water. The ethanolic extract was more effective against lipid oxidation and spoiled bacteria. Antimicrobial activity against S.typhimurium was found only in ethanolic extract treated-samples. Extraction with ethanol/water mixture is a more effective method than water extraction.